PENINGKATAN MINAT BELAJAR SISWA DALAM PELAJARAN MATEMATIKA DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN FLASH CARD PADA SISWA KELAS II SEKOLAH DASAR NEGERI 004 NONGSA - Mastura (Universitas Islam Negeri Alauddin Makassar, 2022)
This research was carried out with the aim of improving the ability to recognize and remember flat figures using flash card learning media for second grade students at SDN 004 Nongsa in the 2018/2019 academic year. This research is a classroom action research (classroom action research). According to Suharsimi Arikunto, et al (2007: 3) classroom action research is an observation of learning activities in the form of actions that are intentionally raised and occur in a class together. The purpose of this study was to increase students' interest in learning mathematics using flash card learning media for second grade students at SDN 004 Nongsa. The results showed that in the first cycle at the first meeting the percentage of student activity was 34.29%, then at the second meeting the average percentage of student activity was 54.28%. While in the second cycle at the 1st and 2nd meetings, it increased to 74.28% and 88.57%, respectively. The results of the evaluation during the pre-cycle the average value of completeness obtained was 70.57, the first cycle the average value obtained was 78.54 and the second cycle the average value of the students increased to 84.63.